Label‐free proteomic analysis of red blood cell membrane fractions from abdominal aortic aneurysm patients. Issue 7 (August 2014) - Martinez‐Pinna, Roxana; Burillo, Elena; Madrigal‐Matute, Julio; Lopez, Juan Antonio; Camafeita, Emilio; Torres‐Fonseca, Monica Maria; Llamas‐Granda, Patricia; Egido, Jesus; Michel, Jean‐Baptiste; Blanco‐Colio, Luis Miguel; Martin‐Ventura, Jose Luis; Ge, Ying; et al.
<x xml:space="preserve">Abstract</x> Purpose To test whether red blood cell (RBC) membrane composition is modified in abdominal aortic aneurysms (AAA) patients. Experimental design RBC membrane extracts from AAA patients (aortic diameter >3 cm, n = 7) and control subjects (n = 4) were analyzed by a label‐free quantitative MS‐based strategy, using spectral count data. Additional validation was performed by western‐blot. Results Data analysis based on spectral count from MS/MS‐based experiments provided us a signature of 39 proteins differentially expressed in RBC membranes between AAA and controls (changes equal/over 1.515‐fold; p‐values equal/lower 0.05). MS data revealed altered levels of structural membrane proteins (e.g. spectrins and ankyrin), components of the degradation machinery (proteasome subunits), and oxidative stress related proteins (e.g. catalase and peroxiredoxin‐2) among others. Decreased catalase and peroxiredoxin‐2 expression in RBC membrane of AAA patients compared to controls were further validated by Western blot, confirming the proteomic results. Conclusions and clinical relevance RBCs membrane protein composition is altered in AAA patients, which could be involved in the pathological role of RBCs in aortic tissue and become potential targets to prevent AAA progression.